Analisis Sentimen Opini Pelanggan Terhadap Aspek Pariwisata Pantai Malang Selatan Menggunakan TF-IDF dan Support Vector Machine - Yoga Tika Pratama; Fitra Abdurrachman Bachtiar; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Department of Tourism and Culture (Disparbud) of Malang Regency requires the customer's perspective in the process of monitoring and evaluation of management and development activities of South Malang beach tourism. But Disparbud neither have the data about the customer's opinion, nor the application of technology on data processing and data analysis that capable of providing information about customer's perspective on aspects of South Malang beach tourism. The customer's perspective can be obtained from customer's opinions in the form of review that available on the web platform. Web Scraping is a method for extraction of customer's opinion data sourced from the web platform. To get the information about customer's perspective on aspects of South Malang beach tourism could be done by performing Aspect Level Sentiment Analysis on the customer's opinion data. One of many classification methods is the Support Vector Machine, which can be used to classify sentiments in sentiment analysis process. This research managed to get 674 customer's opinion data in Bahasa Indonesia ranged from 2013 to 2018 for 43 tourist attractions of South Malang beach tourism sourced from TripAdvisor. The tests that have been conducted on the results of the sentiment classification for all aspects resulted good results in an average of 85% on accuracy, 85% on precision, 87% on recall, and 85% on F1-Score. The output of this research is in form of data visualization in the form of Dashboard consisted of 4 Dashboards which contains results from the process of sentiment analysis on the customer opinions to aspects of South Malang beach tourism.